Adaptive expertise in medical education: Accelerating learning trajectories by fostering self-regulated learning. (3rd August 2018) - Lajoie, Susanne P.; Gube, Maren
Abstract: Medical school is designed to provide students with the necessary education and training needed to be effective and safe physicians. Debates about how best to instruct medical students along this trajectory are abundant. Students learn through a planned curriculum as well as a self-directed one motivated by their own level of interest and ability to access and integrate the exponential growth of medical information available through technology. The rate of change in clinical findings means that some of what is learned in today's classroom will likely be out of date by the time of graduation. To achieve and maintain expertise, students are faced with this challenge. This article explores ways to support medical students in acquiring the skills they need to become adaptive experts. In particular, instructional strategies for supporting the acquisition of fast, accurate, and superior reproducible performance are described with an emphasis on self-regulated learning where students learn to learn flexibly, seeking out opportunities to take knowledge to new levels.